«Tormenta» on the Net: appropriation of images and social protest around a soap opera - Álvarez, Silvia G. (2007)
In the context of virtual communication systems, the new rationale of social participation and the mechanisms used for the appropriation of the resources, contents and meanings that are broadcast through telematic networks are analyzed here from a political anthropology viewpoint. A case study is used in this paper to highlight how a globalized protest is developed against the presentation of a South American soap opera, La Tormenta (The Storm), which was broadcast on the Internet. Users’ capacity for action to convert the Network into ameans of organization and critique and collectively react against the power of the media is analyzed here. This political action went beyond the virtual field to the real world, thus allowing the recognition of rights. This uprise in the network of consumers of cultural products has contributed to transform conventional mechanisms of citizen participation, using the social and emotional connections provided by the new information technologies.